2015
DOI: 10.5423/ppj.oa.01.2015.0014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bt-cotton Genotypes for Resistance to Cotton Leaf Curl Disease under High Inoculum Pressure in the Field and Using Graft Inoculation in Glasshouse

Abstract: Bt-cotton germplasm, consisting of 75 genotypes was evaluated against cotton leaf curl disease (CLCuD) under high inoculum pressure in the field and using graft inoculation in glasshouse by visual symptom scoring assessments. None of the tested genotype was found disease free under both evaluation tests. Under field conditions in 2011, 3 genotypes were found resistant, 4 moderately resistant, 3 tolerant, 2 moderately susceptible and one susceptible; in 2012, 3 genotypes were tolerant, 7 moderately susceptible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Newly growing cotton plants were inoculated with the virus strain (CLCuV). Data were recorded on the ratio of effective grafts, rate of illness transmission, inactive sum (aver-age time needed for initial symptom look once grafting), and sort of indications created ninety days post vaccination (Akhtar et al, 2015).…”
Section: Virus Transmission and Identificationmentioning
confidence: 99%
“…Newly growing cotton plants were inoculated with the virus strain (CLCuV). Data were recorded on the ratio of effective grafts, rate of illness transmission, inactive sum (aver-age time needed for initial symptom look once grafting), and sort of indications created ninety days post vaccination (Akhtar et al, 2015).…”
Section: Virus Transmission and Identificationmentioning
confidence: 99%
“…The Bt-cotton hybrids were introduced in NW India during the year of 2005 and after that a large number of Btcotton hybrids are introduced for cultivation in this region. Mostly all of the Bt-cotton hybrids are recently observed to be highly susceptible to CLCuD (Akram et al 2013, Godara et al 2015, Akhtar et al 2015. Akram et al (2013) reported that Bt-cotton hybrids are more susceptible host for whiteflies than non-Bt cottons in Pakistan resulting in higher disease incidence in Bt-hybrid cotton.…”
Section: Disease Incidence and Boll Number Reduction In Clcud Infecte...mentioning
confidence: 99%
“…The sick plot technique was used by planting one row of highly susceptible cultivar S-12 after every three rows of screening germplasm to maximize CLCuD inoculum(Iqbal et al 2014). The disease severity was scored as percent disease severity index (DSI) at 60, 90, and 120 days after sowing (DAS), as previously described(Akhtar et al 2015).CLCuD incidence (%) = (Sum of all disease) / (Total number of plants) × 100/6^* *= Rating of maximum disease severity Genomic DNA extraction and SSR analysis The youngest leaves of the parental population and F2 progeny plants were collected in ziplock plastic bags for total genomic DNA extraction. The standard CTAB DNA extraction protocol was followed (Paterson et al 1993).…”
mentioning
confidence: 99%